Endocrinal metabolic regulation on the skeletal system in post-menopausal women - Thapa, Santosh; Nandy, Ananya; Rendina-Ruedy, Elizabeth (Frontiers in Physiology, 2022)
Osteoporosis is one of the most common endocrinologic disorder characterized with inflammatory and incurable chronic bone loss condition. Sexual dimorphism is ubiquitous in the incidence of this disease with post-menopausal population being acutely affected. Sex hormones including estrogen is a crucial regulator of bone mass and is critical for skeletal homeostasis; therefore, deficiency of this hormone post menopause causes an imbalance in skeletal turnover leading to osteoporosis. Estrogen can influence both bone formation as well as resorption by reducing osteoblast activity as well as enhancing osteoclastogenesis. Additionally, estrogen is a potent regulator of systemic metabolism. Recent studies have provided clues that estrogenic effect on bone might also involve alterations in bone cell metabolism and bioenergetic potential. While direct effects of gonadal hormones ability to alter intracellular metabolism of bone cells has not been studied, there is precedence within the literature that this is occurring and contributing to post-menopausal bone loss. This review aims to serve as a perspective piece detailing the prospective role of gonadal hormones regulating bone cell metabolic potential.